Perceptions of media portrayed violence among South Korean college students using Q methodology - Kang Suk Lee; Song Yi Lee (Scientific Reports)
Abstract Although numerous studies examine violence portrayed in the media, few have explored how viewers subjectively perceive it despite the presence of contradictory viewpoints. This study employs Q methodology to investigate South Korean college students’ subjective perceptions of media violence. The Q sample comprises 33 statements, and the P-set includes 17 university students. The analysis reveals three perception types. Type 1 (Media Violence Freedom Advocates) believe that personal values influence media violence and do not view it as a problem. They argue that regulating media violence would infringe on freedom of expression. Type 2 (Media Violence Personal Responsibility Emphasizers) view media violence as a means of portraying social issues and find violent content engaging, assuming that wrongdoers ultimately receive punishment. Lastly, Type 3 (Media Violence Ethics and Regulation Advocates) supports regulating media violence and implementing appropriate educational initiatives to address this issue. Understanding these perspectives among college students provides valuable insights for developing media regulations and educational policies.